Pelaksanaan Sustainability Report Berdasarkan GRI Standards Guidelines Pada Perusahaan Manufaktur di Indonesia - Widya Ananda; Hafid Aditya Pradesa; Reni Wijayanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The primary objective of this study is to conduct an analysis of sustainability reports based on the GRI Standard Guidelines among manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study focuses on sustainability reports for the years 2019-2021, which were consecutively published on the official websites of the selected manufacturing companies. Employing a purposive sampling technique, a total of 21 manufacturing companies were included in the study, covering three distinct research periods, thereby resulting in the analysis of 63 data units. The research methodology involves descriptive statistics and utilizes quantitative content analysis methods. The findings of this study reveal that, during the 2019-2021 timeframe, none of the manufacturing companies listed on the IDX have provided comprehensive disclosure of all 89 GRI Standard indicator items in their sustainability reports. Furthermore, when categorizing the implementation levels of sustainability reports as "below average" or "above average," based on a comparison of the average index values among individual companies and all manufacturing companies, it is evident that larger-scale companies (with a market capitalization exceeding IDR 10 trillion) in the "above average" category have exhibited better adherence to sustainability reporting practices compared to smaller-scale companies (with a market capitalization below IDR 10 trillion). Additionally, the analysis indicates that the implementation of economic, environmental, and social aspects of sustainability reporting has shown steady improvement over the years among manufacturing companies. This suggests that while there has been progress, some companies are still not fully aligning with GRI Standards in their reporting practices.For future researchers, it is recommended to extend the analysis to cover a minimum of five reporting periods (years) to gain a more precise understanding of the evolving trends in sustainability reporting implementation. This expanded timeline will enable researchers to assess the progress made by companies in adapting their sustainability reports to conform with GRI Standards more accurately.